2004
DOI: 10.1111/j.1525-1314.2004.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of fluorite and titanite in a calc‐silicate rock from the Vizianagaram area, Eastern Ghats Belt, India

Abstract: In the Vizianagaram area (E 83°29.442¢; N 18°5.418¢) of the Eastern Ghats Belt, India, a suite of graphite-bearing calc-silicate granulites, veined by syenitic rocks, developed wollastonite-rich veins at 6-7 kbar and > 850°C. During subsequent near-isobaric cooling wollastonite was replaced by calcite + quartz and a graphic intergrowth of fluorite + quartz ± clinopyroxene. Titanite with variable Al and F contents is present throughout the rock. Combining the compositional variation of titanite and recent exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
(167 reference statements)
0
4
0
Order By: Relevance
“…Chakhmouradian, 2004), hence, niobian titanite is typically a low-T mineral. Concerning Al,F-rich but Nb(Ta)-free titanite, it is stable over a very wide range of P-T conditions from high-grade metamorphic rocks of eclogite facies (Markl and Piazolo, 1999;Castelli and Rubatto, 2002;Sengupta et al, 2004) to lowgrade metasediments (Enami et al, 1993).…”
Section: Comparison With Other Niobian Titanite Occurrencesmentioning
confidence: 99%
“…Chakhmouradian, 2004), hence, niobian titanite is typically a low-T mineral. Concerning Al,F-rich but Nb(Ta)-free titanite, it is stable over a very wide range of P-T conditions from high-grade metamorphic rocks of eclogite facies (Markl and Piazolo, 1999;Castelli and Rubatto, 2002;Sengupta et al, 2004) to lowgrade metasediments (Enami et al, 1993).…”
Section: Comparison With Other Niobian Titanite Occurrencesmentioning
confidence: 99%
“…Increased fluorine concentrations are indicated by F-bearing minerals in a wide variety of deep metamorphic settings (Bohlen & Essene 1978;Zhu & Sverjensky 1992;Pradeepkumar & Krishnanath 1996;Markl & Piazolo 1998;Tsunogae et al 2003;Sengupta et al 2004). Increased fluorine concentrations are indicated by F-bearing minerals in a wide variety of deep metamorphic settings (Bohlen & Essene 1978;Zhu & Sverjensky 1992;Pradeepkumar & Krishnanath 1996;Markl & Piazolo 1998;Tsunogae et al 2003;Sengupta et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorine plays an important role in metal complexing during fluid-rock interaction at high pressure (P) and temperature (T). Increased fluorine concentrations are indicated by F-bearing minerals in a wide variety of deep metamorphic settings (Bohlen & Essene 1978;Zhu & Sverjensky 1992;Pradeepkumar & Krishnanath 1996;Markl & Piazolo 1998;Tsunogae et al 2003;Sengupta et al 2004). Fluorine-rich fluids can strongly influence the distribution of Ti and other high field-strength elements (HFSE), rare earth elements (REE; light rare earth elements, LREE; heavy rare earth elements, HREE), and U and Th during metamorphism and partial melting (Oreskes & Einaudi 1990;Peterson et al 1991;Pan & Fleet 1996;Rudnick et al 2000;Klemme 2004;Jiang et al 2005;Rapp et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Titanite in the calc-silicates of these workers contains 2.58 wt.% Al 2 O 3 and 0.56 wt.% FeO t , and our Bahrah titanite contains up to 3.25 and 1.77 wt.%, respectively. Sengupta et al (2004) concluded that chemistry of titanite in calc-silicate rocks is controlled by the coexisting fluids and mobility of Al 3+ rather than by pressure, temperature, and whole-rock composition. However, role of Al 3+ in titanite from calcsilicates, either formed by regional metamorphism under high pressure or by a metasomatic thermal effect, is not well understood as titanite in both cases has low Al content (Ye et al 2002).…”
Section: Titanitementioning
confidence: 98%